2000
DOI: 10.1136/gut.47.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variations in survival for colorectal cancer in Europe: a EUROCARE high resolution study

Abstract: Results-Three year observed survival rates ranged from 25% (Cracow) to 59% (Modena), and were low in the Thames area (UK) (38%). Survival rates between registries for "resected" patients varied less than those for all patients. When age, sex, and site were considered, RRs ranged from 0.7 (95% confidence intervals (CI) 0.6-0.9) (Modena) to 2.3 (95% CI 1.9-2.9) (Cracow). After further adjustment by stage, between registry RR variation was between 0.8 (95% CI 0.6-0.9) and 1.8 (95% CI 1.5-2.2). Inter-registry RR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
151
3
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(170 citation statements)
references
References 10 publications
9
151
3
7
Order By: Relevance
“…Differences in health awareness and early detection, and the availability, development of and accessibility to cancer treatment within the population should also be considered. 24,25 In our study, the age-standardized 5-year survival for all cancers combined in China was 30.9%, much lower than has been reported for developed countries. In the United States, for example, five-year relative survival for all cancers combined was 67.2% for adults in 2004, 23 and the corresponding Australian estimate (2006-2010) was 66%.…”
Section: Discussioncontrasting
confidence: 70%
“…Differences in health awareness and early detection, and the availability, development of and accessibility to cancer treatment within the population should also be considered. 24,25 In our study, the age-standardized 5-year survival for all cancers combined in China was 30.9%, much lower than has been reported for developed countries. In the United States, for example, five-year relative survival for all cancers combined was 67.2% for adults in 2004, 23 and the corresponding Australian estimate (2006-2010) was 66%.…”
Section: Discussioncontrasting
confidence: 70%
“…While Iater reports of EUROCARE showed that although survival was improving, inter-country variation is still r_rsisting, suggesting room for further improvement. 5 • 1 Even in high-income countries with well established guidelines and a similar healthcare structure, the difference in outcome is unexplained and vast. 11 Highly relevan!…”
Section: Discussionmentioning
confidence: 99%
“…It is right that such inconsistencies should be pointed out; in fact they were not unexpected given that the study periods differ, and survival rates are changing. These authors highlighted in particular that in the HR study (Gatta et al, 2000) the population of the Modena registry did not perfectly coincide with that presented in the EUROCARE II monograph. * Clearly further HR studies on larger samples are required to clarify how much intercountry survival differences are due to differential delay in diagnosis and how much to differences in treatment.…”
mentioning
confidence: 87%
“…As a consequence, the results are uncertain and the conclusions preliminary. The paper by Woodman et al draws attention to several inconsistencies between survival rates estimated from a few hundred cases included in the recent HR study (Gatta et al, 2000) and those obtained from many thousands of cases diagnosed in a previous period and included in the main EUROCARE II study. It is right that such inconsistencies should be pointed out; in fact they were not unexpected given that the study periods differ, and survival rates are changing.…”
mentioning
confidence: 99%